Ischemia-Challenged human umbilical vascular endothelial cells: Proteomics data - Yaping Ma (Data in Brief, 2021)
[Human umbilical vascular endothelial cells (HUVECs) underwent ischemia, ischemia/reperfusion and normal control (sham) treatment and marked as group I, IR and NC, respectively, were detected by quantitative proteomics and bioinformatics analyses. Proteins in Beclin-1/LC3-II-dependent canonical macroautophagy pathway were verified in details. The significantly upregulated proteins encoded by autophagy-related genes (ATGs) included ATG2A, ATG3, ATG4B, ATG5, ATG7, ATG9A, ATG12, ATG16 and ATG101. The significantly enhanced lysosomal proteins comprised Cathepsin B, Cathepsin D, lysosome-associated membrane protein 1 (LAMP1) and LAMP2. However, the differentially expressed proteins excluded Beclin-1, microtubule-associated protein light chain 3 (LC3)-I and LC3-II. Western blot analyses verified that the protein expressions of Beclin-1, LC3-I and LC3-II were neither upregulated nor downregulated in ischemia-challenged HUVECs.]